2018
DOI: 10.1080/16549716.2018.1483638
|View full text |Cite
|
Sign up to set email alerts
|

The role of national health insurance for achieving UHC in the Philippines: a mixed methods analysis

Abstract: Background: Achieving Universal Health Coverage (UHC) has by now become a key health policy goal in many countries and some form of National Health Insurance (NHI) is often used for this. The Philippines has had more than 50 years’ experience with social health insurance and in 1995 established PhilHealth, the country’s national health insurer. Objectives: Analyzing the role of the Philippine NHI scheme in moving towards UHC, identifying potential avenues for improvement as well as indicating challenges and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 19 publications
3
71
0
Order By: Relevance
“…Increasing interest across many LMICs to improve financial protection and achieve universal health coverage has led to widespread reforms which adopt social health insurance schemes (SHIS) (Obermann et al, 2018;Ogundeji et al, 2019). Ghana, for example, commenced its social health insurance scheme in 2003, funded primarily by taxation through the National Health Insurance Levy (70%), social security contributions (17%), investment income (8%), and premiums and registration fees (5%) (Alhassan et al, 2016;Okoroh et al, 2018).…”
Section: Case Study 2: Social Health Insurance Policy Reformsmentioning
confidence: 99%
“…Increasing interest across many LMICs to improve financial protection and achieve universal health coverage has led to widespread reforms which adopt social health insurance schemes (SHIS) (Obermann et al, 2018;Ogundeji et al, 2019). Ghana, for example, commenced its social health insurance scheme in 2003, funded primarily by taxation through the National Health Insurance Levy (70%), social security contributions (17%), investment income (8%), and premiums and registration fees (5%) (Alhassan et al, 2016;Okoroh et al, 2018).…”
Section: Case Study 2: Social Health Insurance Policy Reformsmentioning
confidence: 99%
“…the case of China), or even without any subsidy and with reliance on a contribution (e.g. the case of the Philippines) (Obermann, Jowett and Kwon, ).…”
Section: Key Policy Issues and Challengesmentioning
confidence: 99%
“…Considering the economic conditions of countries, the results of the present study show that most of the interventions have performed in the eld of nancing or nancial protection functions. Thus, most interventions in these countries have focused on the insurance system and targeted the poor people or speci c groups of society [67,75,78,[80][81][82]120]. Also one of the issues that mostly reformed by countries is the payment and premium systems [60,65,99,121].…”
Section: Discussionmentioning
confidence: 99%
“…That is why nancing function or the nancial protection dimension and interventions in them can be considered as an essential component of achieving UHC. The results of the study showed that successful interventions in the countries under study have positive results such as, reduction in the intensity of care and decrease in length of hospital stay [60,131], elimination of costs of services that cause overuse of health services [65], allocating a large percentage of income to health [80], reducing out-of-pocket payments [132], and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation